Prevalence of camel trypanosomosis and herders’ knowledge, attitude, and practices towards the disease in the pastoral area of southern Ethiopia - Guyo Kanchora; Rahmeto Abebe (BMC Veterinary Research, 2024)
Abstract Background Surra is a parasitic disease caused by Trypanosoma evansi that threatens the health and productivity of camels. Despite its significant impact on camels in Ethiopia, surra has not received as much attention as diseases in cattle and other domestic animals. The objective of the study was to estimate the prevalence of surra, identify the potential risk factors and assess the traditional knowledge, attitude and practices of camel herders towards the disease. Methods The study used a parasitological and participatory epidemiological (PE) approach. Between February and July 2022, a total of 335 blood samples were collected from camels across three districts and tested using the buffy coat technique. The PE investigation involved six key informant groups consisting of 8 to 12 key persons, and used a semi-structured interview and various PE tools and principles. Result The study found that the prevalence of surra among examined camels was 3.9% (95% CI: 2.1–6.5). The prevalence was significantly higher in camels with a poor body condition score (BCS) (OR = 9.3; 95% CI: 1.8–47.5; p = 0.008) compared with camels with a good BCS. However, district, age, sex, and ethnicity had no effect on the prevalence of surra (p > 0.05). The study also found that the packed cell volume (PCV) was significantly lower (p < 0.0001) in parasitaemic animals (18.92 ± 2.63) than in aparasitaemic animals (25.13 ± 4.56). Camels with poor BCS (22.7 ± 3.5) had a significantly (p < 0.001) lower mean PCV than camels with good BCS (26.2 ± 5.0). The PE investigation showed that all the camel herders were well aware of surra, known locally as Dhukana. The clinical symptoms, the season of high incidence, routes of transmission, impact on production, and control methods were accurately described. Moreover, this study emphasized that surra is the primary disease affecting camel health and productivity. Conclusion The study identified a moderate prevalence of surra in the research area. To reduce surra incidence and associated losses, enhancing veterinary services and providing support for proper camel husbandry practices in the region is recommended. Additionally, future studies should consider using more sensitive and specific techniques like serological and molecular assays, as this study relied on microscopy only.